Total quality management and performance management systems: team players or lonely riders?. (7th June 2018) - Peljhan, Darja; Marc, Mojca
Abstract : The paper investigates the joint effects of using total quality management (TQM) and performance management systems (PMSs) on the importance managers place on five different performance perspectives. Our study extends the current knowledge on the simultaneous use of multiple managerial concepts. Contrary to other studies of TQM and PMSs, we take into account that their effects are not independent from the use of other managerial concepts. Controlling for contextual variables and the use of other managerial concepts, we test the effects of joint TQM-PMS use on cross-section data from a sample of 264 companies. We find that the joint use is associated with a decrease in the perceived importance of customer perspective. This implies that only the importance of the customer measures changes for managers because they use TQM and PMS. One possible explanation for this result is that TQM companies over-emphasise the customer perspective which is 'counter-balanced' if PMS is jointly used. For other perspectives (employee, operational, return, and financial), we find only weak evidence of interdependencies between TQM and PMSs.